ANALISIS NILAI TAMBAH KERIPIK PISANG PADA INDUSTRI CAHAYA INDI DI DESA TANAMEA KECAMATAN BANAWA SELATAN KABUPATEN DONGGALA - Uun Angriani; Alimudin Laapo; Dafina Howara (Universitas Tadulako, 2014)
This study aims to determine how much added value from processing the raw bananas into banana chips. Determination of respondent committed intentionally (purposive), with the consideration that business and labor leaders of home industry cahaya Indi can provide valid information about the banana chips processing and required data. Respondents in this research were the company leaders and three employees. The data collecting in this research consisted of primary and secondary data. Data analysis tool used is the value-added analysis. The results showed that the Home Industry cahaya Indi gains profit of Rp. 15.492.365 for 8 times production process in a month and the added value obtained is Rp. 9,462 per kilogram of raw material used. Key words : Analysis, value-added, banana chips, Industry Cahaya Indi.